2015
DOI: 10.1111/asj.12397
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor is pro‐adipogenic in rat skeletal muscle progenitor clone, 2G11 cells

Abstract: Intramuscular adipose tissue (IMAT) formation is a hallmark of marbling in cattle. IMAT is considered to originate from skeletal muscle progenitor cells with adipogenic potential. However, the mechanism involved in IMAT formation from these progenitor cells in vivo remains unclear. In the present study, among the growth factors tested, which were known to be expressed in skeletal muscle, we found only basic fibroblast growth factor (bFGF) has a pro-adipogenic effect on skeletal muscle derived adipogenic progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…In sarcopenia, muscle frequently exhibits adipose- and fibrous-tissue infiltration [ 14 ], and this impairs skeletal muscle function: whereas intramuscular adipose tissue (IMAT) causes poor physical performance [ 15 ], fibrous tissue reduces motile and contractile functions [ 16 ]. Both IMAT and fibrous tissue have been widely shown to be derived from mesenchymal progenitor cells (MPCs), which reside in the interstitial space in skeletal muscle [ 17 , 18 ] and whose fibro/adipogenic potential is regulated by secreted growth factors: TGFβ upregulates the expression of the fibroblast markers collagen type 1 (Col1a1), connective-tissue growth factor (CTGF), and α-actin-2 (Acta2) [ 19 ], and basic fibroblast growth factor (bFGF) promotes the adipogenic programme of skeletal muscle adipogenic cells, as we reported previously [ 20 ]. Moreover, MPCs provide functional support to satellite cells and promote muscle regeneration [ 17 ].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…In sarcopenia, muscle frequently exhibits adipose- and fibrous-tissue infiltration [ 14 ], and this impairs skeletal muscle function: whereas intramuscular adipose tissue (IMAT) causes poor physical performance [ 15 ], fibrous tissue reduces motile and contractile functions [ 16 ]. Both IMAT and fibrous tissue have been widely shown to be derived from mesenchymal progenitor cells (MPCs), which reside in the interstitial space in skeletal muscle [ 17 , 18 ] and whose fibro/adipogenic potential is regulated by secreted growth factors: TGFβ upregulates the expression of the fibroblast markers collagen type 1 (Col1a1), connective-tissue growth factor (CTGF), and α-actin-2 (Acta2) [ 19 ], and basic fibroblast growth factor (bFGF) promotes the adipogenic programme of skeletal muscle adipogenic cells, as we reported previously [ 20 ]. Moreover, MPCs provide functional support to satellite cells and promote muscle regeneration [ 17 ].…”
Section: Introductionmentioning
confidence: 76%
“…To investigate whether senescence affects the adipogenic potential of 2G11 cells, PMS-2G11 cells were treated with bFGF, which exerts a pro-adipogenic effect on skeletal muscle adipogenic cells [ 20 ]. We immunocytochemically analysed Peroxisome proliferator-activated receptor (PPAR) γ and perilipin to assess adipogenicity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, 2G11 cells are considered to be a useful MPC clone to elucidate the regulatory mechanism involved in fibrogenic/adipogenic differentiation of MPC. By using 2G11 cells as a model of MPC, we also reported that basic fibroblast growth factor (bFGF) has a pro‐adipogenic effect on MPC (Nakano et al, 2016). Therefore, it is possible that differentiation fate of MPC is regulated by the cross talk between TGF‐β and FGF signals.…”
Section: Introductionmentioning
confidence: 99%